The passing of postmodernism a spectroanalysis of the contemporary - Toth, Josh (SUNY series in postmodern culture, 2010)
Examines the increasingly prevalent assumption that postmodernism is over and that literature and film are once again engaging sincerely with issues of ethics and politics.
Keywords: Derrida, Jacques : Criticism and interpretation; Postmodernism (Literature); Semiotics and literature; Criticism; Poststructuralism